2020
DOI: 10.1186/s12866-020-02009-w
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and typing of the methicillin-resistant Staphylococcus aureus clones in Kuwait hospitals, 2016–2017

Abstract: Background Methicillin-resistant Staphylococcus aureus (MRSA) belong to diverse genetic backgrounds that differ in antibiotic resistance. Knowledge of the local clonal composition of MRSA strains is important for patients’ management and for designing effective control and eradication methods. The aim of this study was to compare the antibiotic resistance patterns and genotypic characteristics of MRSA isolates obtained in public hospitals in Kuwait in 2016 and 2017 for changes in their resistance patterns and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 34 publications
(50 reference statements)
6
16
2
Order By: Relevance
“…Isolates of other CCs (CC5, CC97) and of spa-types assignable to other CCs were most frequently observed in meat from sheep in 2020 (5/11 isolates). CC97 isolates have previously been associated with bovines (K € appeli et al, 2019) and pigs in Italy (Feltrin et al, 2015), but they have also been observed in human cases unrelated to animal production (Monecke et al, 2011;Boswihi et al, 2020). Therefore, their origin in food is doubtful.…”
Section: Typing Results Of Mrsa From Animals and Foodmentioning
confidence: 99%
“…Isolates of other CCs (CC5, CC97) and of spa-types assignable to other CCs were most frequently observed in meat from sheep in 2020 (5/11 isolates). CC97 isolates have previously been associated with bovines (K € appeli et al, 2019) and pigs in Italy (Feltrin et al, 2015), but they have also been observed in human cases unrelated to animal production (Monecke et al, 2011;Boswihi et al, 2020). Therefore, their origin in food is doubtful.…”
Section: Typing Results Of Mrsa From Animals and Foodmentioning
confidence: 99%
“…MRSA has been mentioned in the EU/EEA (EARS-Net) Annual Epidemiological Report for 2019 as one of the most common causes of bloodstream infections, exhibiting a high burden in terms of morbidity and mortality [44]. These strains have become a severe clinical and epidemiological problem, as resistance to methicillin implies resistance to all β-lactam antibiotics [45]. The violet crystal quantification of biofilm formed on polystyrene surfaces in the presence of different concentrations of the complexes showed that both compounds were able to inhibit biofilm formation at the initial stage by reducing the expression of adhesion proteins, with the minimal biofilm eradication concentration (MBEC) values ranging from 0.71 to 0.04 mM (Table 7).…”
Section: Microbiological Assaymentioning
confidence: 99%
“…Molecular typing tools including staphylococcal protein A (spa) typing, multilocus sequence typing (MLST), pulsed-field gel electrophoresis, staphylococcal cassette chromosome mec (SCC mec ) typing, DNA microarray, and whole genome sequencing (WGS) have been used in the epidemiologic surveillance of MRSA strains to detect and monitor emerging and reemerging infections as well as monitoring geographic spread and shifts of epidemic and endemic clones ( Pfaller, 1999 ; van Belkum et al, 2001 ; Monecke et al, 2011 ; Boswihi et al, 2016 , 2020a , 2020b ; Rebic et al, 2016 ). The application of these typing techniques to type MRSA from different geographic regions have shown that most of the MRSA infections reported worldwide were caused by a limited number of pandemic MRSA clones belonging to clonal complexes 5 (CC5), CC8/ST239, CC22, CC30, and CC45 ( Robinson and Enright, 2003 ; Monecke et al, 2011 ; Guthrie et al, 2020 ) although CA-MRSA isolates belong to more diverse genetic backgrounds compared to HA-MRSA ( Monecke et al, 2011 ; Udo, 2013 ; Tong et al, 2015 ; Guthrie et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus strains belonging to CC361 (CC361-MRSA) were described as rare and were reported sporadically in humans ( Afroz et al, 2008 ; Weber et al, 2010 ; Coombs et al, 2011 ; Monecke et al, 2011 ; Shambat et al, 2012 ; Kinnevey et al, 2014 ), Rhesus monkeys ( Roberts et al, 2019 ), Cattle ( Tegegne et al, 2017 ), and in ready-to-eat food items ( Islam et al, 2019 ). However, the CC361-MRSA have been increasingly isolated from human patients in the Arabian Gulf countries of Saudi Arabia ( Senok et al, 2019 ), United Arab Emirates ( Senok et al, 2020 ) and Kuwait ( Boswihi et al, 2018 , 2020a , 2020b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation